PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE TERHADAP PENINGKATAN COLLABORATION SKILL DAN HASIL BELAJAR SISWA KELAS X E1 DAN X E4 EKONOMI DI SMA NEGERI 3 BUKITTINGGI - Angraini, Sartika; Elikal Marna, Jean (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to determine the effect of the Think Pair Share (TPS) cooperative learning model on students' learning outcomes in Economics. The TPS model is believed to improve learning outcomes through paired activities and idea sharing that encourage active student engagement. The problem underlying this research is the low level of students’ collaboration skills and learning outcomes in Economics, as indicated by a lack of active participation and limited understanding of the subject matter. The learning approach, which is still dominated by lecture-based methods, tends to make students passive and less involved in the learning process. Through the implementation of the TPS model, it is expected that students will be more actively engaged in discussions, problem-solving, and decision-making, which in turn can enhance their learning outcomes. This research was conducted at SMA Negeri 3 Bukittinggi, with class X E1 as the control group and class X E4 as the experimental group. The study employed a quantitative approach using a quasi-experimental design with a Pretest-Posttest Control Group Design. The sample was selected using purposive sampling. The research instruments consisted of an observation sheet to assess collaboration skills and a learning outcome test. The hypothesis was tested using an independent sample t-test. The results showed that the implementation of the Think Pair Share (TPS) model significantly increased students’ learning motivation and outcomes compared to conventional learning methods. This was evidenced by improvements in both collaboration skills and learning outcomes after applying the TPS model. It can be concluded that the Think Pair Share (TPS) learning model effectively enhances students’ motivation and academic performance.